ANALISIS PRODUKTIVITAS DAN EFEKTIVITAS TENAGA KERJA INSTALASI PEMELIHARAAN FASILITAS NON MEDIS RSUD DR. MOEWARDI, SURAKARTA - Atifudin, Atifudin; Martono, Martono; Rochadi, Mochammad Tri (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2016)
Non Medical Maintenance Facility of RSUD Dr. Moewardi, Surakarta as one ofe local hospital have a maintenance organization and care set and run such activities planing, inspection, maintenance, and repair pertaining to facilities so far. An organization rearing and care a building need to know levels of productivity each labor that labor you have available can work effectively and efficiently. Method used to perfoming calculations productivity adn effectiveness labor which there is method of analysis toward their job don submarine two years count of january 2014 until december 2015. From analysis that has been done productivity an effectiveness labor which is with Non Medical Maintenance Facility of RSUD Dr. Moewardi, Surakarta be seen that productivity and effectiveness mean labor for two years to labor work of water amounting to 21,74% and 25,15%, labor employement of electric power of 18,54% and 13,35%, labor work comumication 0f 8,58% and 17,76% labor for a job the elevator 0f 17,36% and 14,24%.Kata kunci :